Purification and partial characterization of a coagulant serine protease from the venom of the Iranian snake Agkistrodon halys - Ghorbanpur,M (2009)
Agkistrodon halys is one of several dangerous snake species in Iran. Among the most important signs and symptoms in patients envenomated by this snake is disseminated intravascular coagulation. A thrombin-like enzyme, called AH143, was isolated from Agkistrodon halys venom by gel filtration on a Sephadex G-50 column, ion-exchange chromatography on a DEAE-Sepharose and high performance liquid chromatography (HPLC) on a C18 column. In the final stage of purification, 0.82 mg of purified enzyme was obtained from 182.5 mg of venom. The purified enzyme showed a single protein band by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), under reducing conditions, and its molecular mass was found to be about 30 kDa. AH143 revealed clotting activity in human plasma, which was not inhibited by EDTA or heparin. This enzyme still demonstrated coagulation activity when exposed to variations in temperature and pH ranging, respectively, from 30 to 40°C and from 7.0 to 8.0. It also displayed proteolytic activities on synthetic substrate. The purified enzyme did not show any effect on casein. We concluded that the venom of the Iranian snake Agkistrodon halys contains about 0.45% single procoagulant protein which appears to be a thrombin-like enzyme.